Emerging theragnostic radionuclide applications for hepatocellular carcinoma - Nyakale, N. E.; Aldous, C.; Gutta, A. A.; Khuzwayo, X.; Harry, L.; Sathekge, M. M. (Frontiers in Nuclear Medicine, 2023)
Hepatocellular carcinoma (HCC) is a major global health problem. Theragnostic is a term that refers to the integration of diagnostic and therapeutic modalities into a single system for personalized medicine. Theragnostic care in HCC involves the use of imaging techniques to diagnose the cancer and assess its characteristics, such as size, location, and extent of spread. Theragnostics involves the use of molecular and genetic tests to identify specific biomarkers that can help guide treatment decisions and, post-treatment, assess the dosimetry and localization of the treatment, thus guiding future treatment. This can be done through either positron emission tomography (PET) scanning or single photon emission tomography (SPECT) using radiolabeled tracers that target specific molecules expressed by HCC cells or radioembolization. This technique can help identify the location and extent of the cancer, as well as provide information on the tumor's metabolic activity and blood supply. In summary, theragnostics is an emerging field that holds promise for improving the diagnosis and treatment of HCC. By combining diagnostic and therapeutic modalities into a single system, theragnostics can help guide personalized treatment decisions and improve patient outcomes.